2018
DOI: 10.2106/jbjs.st.18.00017
|View full text |Cite
|
Sign up to set email alerts
|

Knee Arthroscopy

Abstract: Background: Virtual reality and cadaveric simulations are expensive and not readily accessible 1. Innovative and accessible training adjuncts are required to help meet training needs. Cognitive task analysis (CTA) has been used extensively to train pilots and surgeons in other surgical specialties 2-6. However, the use of CTA tools within orthopaedics is in its infancy. Arthroscopic procedures are minimally invasive and require a different skill set compared with open surgery. Residents often feel poorly prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…18 , 46 Studies have suggested they improve residents’ acquisition of both technique and knowledge within laparoscopic 14 , 44 and robotic 40 procedures, including flexor tendon repairs 30 and colonoscopies. 47 In orthopaedics, there is evidence demonstrating the effectiveness of CTA in training novices in knee arthroscopy, 7 , 8 femoral intramedullary nailing, 9 and total hip arthroplasty. 28 However, there are no reported studies of CTA in meniscal repair.…”
mentioning
confidence: 99%
“…18 , 46 Studies have suggested they improve residents’ acquisition of both technique and knowledge within laparoscopic 14 , 44 and robotic 40 procedures, including flexor tendon repairs 30 and colonoscopies. 47 In orthopaedics, there is evidence demonstrating the effectiveness of CTA in training novices in knee arthroscopy, 7 , 8 femoral intramedullary nailing, 9 and total hip arthroplasty. 28 However, there are no reported studies of CTA in meniscal repair.…”
mentioning
confidence: 99%